Secondary coverage configuration to support surveillance monitoring - Altahir, A.A. (Institute of Electrical and Electronics Engineers Inc., 2015)
The ability of modeling the camera backup coverage is evidently crucial to meet the requirements of security monitoring and to plan the surveillance system accordingly. One of the modeling methods is to geometrically compute the coverage based on the sensor capabilities. Besides the visibility challenges related to the arbitrary scenarios, the secondary coverage representation and calculation is also an issue. This work extended an existing geometrical coverage model to consider the overlapping calculations occurred within the adjacent cameras. The backup coverage calculation is realized based on a combination of imagery and computer graphic techniques. As proven by the simulation results, the proposed approach is capable of computing the camera coverage overlapping area in highly practical and accurate manner. Â© 2015 IEEE.